Lead biosorption and chemical composition of extracellular polymeric substances isolated from mixotrophic microalgal cultures - Wioleta Ciempiel; Magdalena Czemierska; Dariusz Wiącek; Marlena Szymańska; Anna Jarosz-Wilkołazka; Izabela Krzemińska (Scientific Reports)
Abstract Extracellular polymers (EPS) produced by microalgae are considered an important factor in the process of biosorption of environmental contaminants. The study investigated the impact of mixotrophic cultivation of unicellular algae Chlorella vulgaris, Parachlorella kessleri, and Vischeria magna on the specific productivity and yield of total and soluble EPS as well as the biochemical composition and sorption properties of extracellular polymers in order to explore their potential to be used for biosorption. The results showed that the mixotrophic conditions enhanced the productivity and contributed to changes in the biochemical and monomer composition of EPS. Higher levels of total sugars, reducing sugars, protein, and phenolic compounds and reduced content of uronic acids were observed in the EPS isolated in the mixotrophic conditions. Rhamnose, xylose, mannose, glucose, and galactose were detected in the mixotrophic EPS samples. FTIR and ICP-OES were applied to characterise the structure of EPS and their role in Pb(II) removal. The results showed that the carboxyl groups and hydroxyl groups observed in the mixotrophic EPS played an important role in the Pb(II) sorption process. The EPS from the mixotrophic C. vulgaris cultures showed the highest potential for the removal of Pb(II) and the highest sorption capacity.